Synthesis of 1,2-Disubstituted Acenaphthylenes by Palladium-Catalyzed Annulation Reactions of Dibromoarenes with Internal Alkynes - An, Wenbo; Li, Gaoqiang; Ma, Jun; Tian, Youping; Xu, Feng (Synlett, 2014)
A simple and versatile route to 1,2-disubstituted acenaphthylenes has been developed. The method involves palladium-catalyzed annulation of 1,8-dibromonaphthalene or 5,6-dibromoacenaphthylene with an internal alkyne, and does not require any organometallic reagent. A range of 1,2-disubstituted acenaphthylenes and 5,6-disubstituted 1,2-dihydrocyclopenta[f,g]acenaphthylenes were prepared in moderate to good yields. The method provides a rapid and simple route to dibenzo[j,l]fluoranthene through an Ullmann coupling.
Keywords: arenes; polycycles; annulations; cross-coupling; domino reactions